Production of Functional Vinegar Enriched with γ-Aminobutyric Acid through Serial Co-Fermentation of Lactic Acid and Acetic Acid Bacteria Using Rice Wine Lees - Yun-Ho Park; Min-Jeong Kwon; Dong-Min Shin; Sam-Pin Lee (Applied Microbiology)
Functional vinegar with high γ-aminobutyric acid (GABA) content was manufactured through a two-stage serial co-fermentation of rice wine lees, a by-product of Korean rice wine, using lactic acid bacteria (LAB) and acetic acid bacteria (AAB). The first LAB fermentation elevated GABA content by utilizing monosodium glutamate (MSG) as a precursor. Lactiplantibacillus plantarum KS2020 converted up to 10% of MSG into GABA and indicated a GABA content of 65.49 mg/g. The concentration of LAB-fermented rice wine lees was then optimized for the second co-fermentation, and Acetobacter aceti was used to produce vinegar. Co-fermentation using 40% first LAB-fermented rice wine lees yielded vinegar with 55.34 mg/g acetic acid and 22.61 mg/g GABA. The temperature-dependent reduction in GABA in GABA-enriched vinegar followed the Arrhenius relationship during storage, with an activation energy of 9.94 kcal/mol (20–35 °C, R2 = 0.99). The GABA present in the vinegar showed evidence of a temperature-/time-dependent decrease, decreasing by 40% over five months. This study first proved the higher GABA-enriched vinegar production from rice wine lees using Lb. plantarum KS2020 and A. aceti.